Developing pre-service teachers' confidence: real-time coaching in teacher education. Issue 6 (1st November 2016) - Stahl, Garth; Sharplin, Erica; Kehrwald, Ben
Abstract: Teacher quality continues to be of major concern in the Western world, and identifying the most effective approach to teacher training remains a contested area. It has been argued that teachers resist change because they lack motivation, have inadequate knowledge and expertise to modify their practices, and are reluctant to take risks for fear of having their confidence damaged. While remaining skeptical of such a deficit view, our interest is in pedagogic approaches which seek to better prepare teachers for teaching in contemporary society and, thus, to enhance their 'effectiveness.' This article discusses the use of a Real-Time Coaching (RTC) model designed to enhance pre-service teachers' practical skills for contemporary classroom teaching. The model focuses upon pre-service teachers micro-teaching while simultaneously gaining feedback via a headset in real time; this is then combined with multiple collaborative feedback cycles within a learning community in order to foster reflective practice. To collect information about participants' experiences with the RTC process, two rounds of semi-structured interviews were conducted with participants. Our findings indicate the RTC model has the capacity to foster a sense of confidence and ownership of learning by developing practical skills alongside affective attributes such as resilience, efficacy, and a disposition toward continual improvement.